The The Influence of Leadership Style on Employee Performance: A Systematic Literature Review : A Systematic Literature Review - Tamimi, Muhizan; Sopiah, Sopiah (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2022)
Purpose – This systematic literature review aims to synthesize several studies related to the influence of leadership style on employee performance. Methodology/approach – This study was compiled using Preferred Reporting Items for Systematic Review and Meta-Analysis from research related to the influence of organizational culture on employee performance. The data collection method uses the Population, Intervention, Comparison, and Outcome methods using 2 accesses, namely Google Scholar and Wiley Online Library. A total of 259 data were filtered using data inclusion criteria so that 30 data were obtained that were by the eligibility standards. Findings – it was found that there were forty-five (45) hypotheses related to leadership style and employee performance. Based on the effect and function of the data variables, they are grouped into four (4), namely, a significant positive effect, no influence and mediating variables, and moderating variables. Novelty/value – Leadership style is a very important factor in the organization because as a vehicle leader in achieving organizational goals. organizational goals can be achieved when employee performance is good. From the many types of leadership styles and various types of organizations, it is necessary to classify various studies related to leadership styles and employee performance in the last 5 years starting from 2017 to 2022.